2003
DOI: 10.1097/01.smj.0000078686.34109.11
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Psychosis by Misinterpretation of Physical Symptoms

Abstract: Impaired processing of perceptual information is often a prominent aspect of psychotic disorders. Physical symptoms such as pain or discomfort may be either incorrectly perceived or misinterpreted by psychotic patients. Presented here is a series of cases in which somatic symptoms occurred in psychotic patients and worsened their psychotic states but only later were recognized as physical problems. Psychotic patients may be unable to comprehend or describe their physical symptoms adequately. Physical disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Delusional disorders are thought to be stable in their course and less than 25% progress to schizophrenia [5]. Impaired or altered processing of perceptual disturbances is common in people suffering from psychotic disorders [6]. Although studies have found a genetic predisposition in those suffering from schizophrenia spectrum disorders and have shown a familial inheritance pattern the same is not true for delusional disorders [5].…”
Section: Introductionmentioning
confidence: 79%
“…Delusional disorders are thought to be stable in their course and less than 25% progress to schizophrenia [5]. Impaired or altered processing of perceptual disturbances is common in people suffering from psychotic disorders [6]. Although studies have found a genetic predisposition in those suffering from schizophrenia spectrum disorders and have shown a familial inheritance pattern the same is not true for delusional disorders [5].…”
Section: Introductionmentioning
confidence: 79%
“…In addition, we wanted to explore the relevance of affective reactivity to a more internal stimulus as well, specifically physical discomfort. Physical discomfort may be misinterpreted by individuals with psychotic experiences (Reeves and Torres, 2003), who therefore may show increased affective response to this stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, impaired processing of perceptual information may lead to physical symptoms being misperceived by patients and clinicians. A series of cases were recently reported in which somatic symptoms occurred in psychotic patients and worsened their psychosis, but only later were recognized as physical problems [26]. Physicians often regard psychotic individuals as unpredictable and limit their clinical contact.…”
Section: Laboratory Testsmentioning
confidence: 98%